Molecular Phylogeny and Ontogeny of a New Ciliate Genus, Paracladotricha salina n. g., n. sp. (Ciliophora, Hypotrichia). (July 2014) - Shao, Chen; Li, Liqiong; Zhang, Qianqian; Song, Weibo; Berger, Helmut
Abstract A hypotrichous ciliate, Paracladotricha salina n. g., n. sp., was discovered in hypersaline waters (salinity about 80‰) from Qingdao, China. Its morphology and some major ontogenetic stages were studied and the phylogenetic position was estimated using standard methods. Paracladotricha salina is characterized by a flexible, more or less slender body (size 50–120 × 20–35 μm), a gonostomatid oral apparatus, one short and two long frontoventral rows, four macronuclear nodules, almost completely reduced dorsal kineties 1–3, and a loss of several parts of the ciliature, namely, the slightly shortened ciliary row of the adoral membranelles, the paroral, and the buccal, the postoral and pretransverse ventral, the transverse, and the caudal cirri. The ontogenesis is rather simple: anlage II of both filial products and anlage III of the opisthe originate de novo, while anlagen IV and V are formed within the parental rows. This combination of features requires the establishment of a new genus, Paracladotricha, which is, according to the morphological data, closely related to Schmidingerothrix and Cladotricha. The small‐subunit rRNA gene was sequenced, indicating that P. salina is, as also demonstrated by the oral apparatus, a member of the gonostomatids. We provide a first, vague hypothesis about the phylogenetic relationships of the Gonostomatidae, Cladotrichidae, and Schmidingerotrichidae. However, since molecular data of the type species of these higher taxa are lacking, their validity and relationships remain obscure.